Optimasi Pemilihan Cafe Terbaik Menggunakan Rank Order Centroid dan Simple Additive Weighting - Yantika, Mega Juni; Mardianto, Mardianto; Ilcham, Ilcham (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2025)
Choosing the optimal café can be difficult due to the necessity of objectively evaluating several variables, including food quality, comfort, pricing, service, and supplementary amenities. This study seeks to enhance the selection process for the optimal cafe by employing the Rank Order Centroid (ROC) approach for criterion weighting and the Simple Additive Weighting (SAW) method for ranking alternatives. Data were collected via questionnaires and firsthand observations of multiple cafés, with criteria assessed according to consumer preferences. ROC was employed to ascertain proportional criteria weights, whereas SAW aggregated normalized values and weights to generate alternative ranks. The findings indicated that Cafe 2 attained the maximum preference score of 0.70, establishing it as the premier recommendation. The integration of ROC and SAW demonstrated efficacy in producing objective, systematic, and transparent outcomes, rendering it suitable for decision support systems that aid consumers in selecting the optimal cafe